KUALITAS RANSUM KOMERSIAL BABI YANG DISIMPAN PADA BEBERAPA LAMA PENYIMPANAN - Tabita Naomi Ralahalu; Shirley Fredriksz; Kadir Kadir (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2018)
The aim of this study was to determine the length of storage time on physical and chemical quality of swine commercial ration. Experimental design used was Randomised Complete design 4 x 5. Variables measured were physical quality, including weight, colour, and odor. Chemical quality such as water content, crude protein, and fat. Mean differences were detected using BNT, The treatment were LP0 = no store ; LP1 = one month store, LP2 = two months store, LP3 = three months store. The result shows that the treatmenthas significant effect on colour, odour and final weight of the ration (P<0.05). The treatment also has significant effect on nutrients content and peroxide number (P<0.05). It can be concluded that the final weight of LP3 ration decrease and was lower than the others, the colour has changed, the odour become tallowy smelling, water content of LP2 is higher, protein content of LP3 decrease, peroxide number of LP3 also decrease.